A new three-dimensional code for OCDMA system - Kadhim, Rasim Azeez (School of Computer and Communications Engineering, 2016)
The scope of this work is detailed in Figure 1.4. An approach of developing a new three-dimensional code is provided to enhance the performance of the three-dimensional spectral/time/spatial OCDMA systems. This work focuses on the proposed code construction and mathematical modelling. Some standard parameters are measured, such as; BER and SNR under the effects of effective received power, data rate, the number of active users and receiver noises. Besides the code construction and mathematical modelling, extensive studies have also been conducted via simulation modelling of the 3-D OCDMA system based on the proposed code.